1145. Reducing Antibiotic Use In Children With Respiratory Syncitial Virus-related Bronchiolitis: Implementation of TeamSTEPPS(®) 2.0 to Improve Pharmacy-Physician Communication in a Community Hospital Antibiotic Stewardship Program - Dutta, Ankhi (Open Forum Infect Dis, 2019)
BACKGROUND: Overuse of antibiotics in Respiratory Syncytial virus (RSV) bronchiolitis in children has been reported between 29–80%. Our antibiotic stewardship program (ASP) utilized a validated communication tool using TeamSTEPPS ® 2.0 principles to improve pharmacy-physician communication and improve audit-feedback technique (AFT). METHODS: We trained pharmacists and physicians in TeamSTEPPS ® 2.0 using simulation-based training. The key component of the training was: closed-loop communication and using a scripted pharmacy communication tool. The scripted pharmacy communication tool was modified from the “DESC” script used in TeamSTEPPS ® 2.0, which includes (1) Describing the situation, (2) Expressing concern, (3) providing Solutions, (4) stating Consequences and coming to an agreement. We incorporated this to improve the audit-feedback technique. We aimed to: (1) Reduce overall percentage of antibiotic (abx) use in RSV bronchiolitis by 25%, (2) reduce use of ceftriaxone, (3) reduce average antibiotic days of therapy (DOT). RESULTS: Our baseline data from 2017–18 RSV season showed a 42% (48/113) use of abx, of which 10% were deemed inappropriate. When compared with the 2018–2019 season, no differences were noted in patient demographics. The median length of stay between the two time periods was similar (2.9 days, IQR 1.9–4.8 days vs. 3.1 days, IQR 2.1–5.1 days, P = 0.17). More patients were admitted to the pediatric intensive care unit (PICU) in the 2018–2019 period: 35/96 (36.4%) as compared with 17/113 (15%) in the previous season. Although similar proportions of patients received abx (42% vs. 41%) in the two groups (Figure 1), average abx DOT, significantly decreased in the 2018–2019 period as compared with 2017–2018 (Figure 2). There was also a decrease in the use of ceftriaxone during the 2018–2019 (Figure 3). All physicians and pharmacists were satisfied with the communication technique and thought that it improved their interaction and understanding of the ASP process. CONCLUSION: Though we did not reduce the overall abx use in RSV bronchiolitis, we did reduce the average abx DOT and use of ceftriaxone in our institution. The use of a validated communication tool to improve prospective AFT was crucial to the success of the ASP program. [Image: see text] [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.